Interventions to improve calcium intake through foods in populations with low intake. Issue 1 (31st January 2022) - Bourassa, Megan W.; Abrams, Steven A.; Belizán, José M.; Boy, Erick; Cormick, Gabriela; Quijano, Carolina Diaz; Gibson, Sarah; Gomes, Filomena; Hofmeyr, G. Justus; Humphrey, Jean; Kraemer, Klaus; Lividini, Keith; et al.
Abstract: Calcium intake remains inadequate in many low‐ and middle‐income countries, especially in Africa and South Asia, where average intakes can be below 400 mg/day. Given the vital role of calcium in bone health, metabolism, and cell signaling, countries with low calcium intake may want to consider food‐based approaches to improve calcium consumption and bioavailability within their population. This is especially true for those with low calcium intake who would benefit the most, including pregnant women (by reducing the risk of preeclampsia) and children (by reducing calcium‐deficiency rickets). Specifically, some animal‐source foods that are naturally high in bioavailable calcium and plant foods that can contribute to calcium intake could be promoted either through policies or educational materials. Some food processing techniques can improve the calcium content in food or increase calcium bioavailability. Staple‐food fortification with calcium can also be a cost‐effective method to increase intake with minimal behavior change required. Lastly, biofortification is currently being investigated to improve calcium content, either through genetic screening and breeding of high‐calcium varieties or through the application of calcium‐rich fertilizers. These mechanisms can be used alone or in combination based on the local context to improve calcium intake within a population.